Infantile cutaneous sarcoidosis. - Crespi, H.; Cordero, A.A.; Abulafia, J.; De Francesco, S.m. (European Journal of Pediatric Dermatology, 2018)
Sarcoidosis is a multisystemic disease, most of the cases starting in adulthood. Pediatric cases are extremely rare, even more in preschool children. Infantile sarcoidosis can be divided in two different clinical forms, according to the age, in older children affecting lungs, lymphatics and eyes, and in preschoolers presenting more prominent compromise of small joints, simulating a juvenile rheumatoid arthritis. with cutaneous and ocular involvement. We report a 2 years old male patient, who has developed sarcoidosis cutaneous lesions, and no other feature until last control. This should be taken in account, because skin manifestations may precede systemic lesions for several months. Our particular case represented a very arduous clinical diagnosis, due to the numerous differential diagnoses to rute out, especially pathologically, such as lepra, tuberculosis, syphilis, systemic mycosis and foreign body granuloma. The treatment was unsuccessful, due to resistance to thalidomide, chloroquine and systemic corticosteroid therapy.